Increasing Teachers’ Capacity in Developing English Lesson Plans to Teachers of Aisyiyah Al Amna Playgroup in Bausasran, Yogyakarta - Iswati, Luluk; Dwi Setyo Hastuti, Saptin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Introducing English since early ages is beneficial, and it is important to equip teachers with adequate lesson planning skills so that the teaching will be effective.  This community service activity aimed to enhance the lesson planning skills of Aisyiyah Al Amna Playgroup teachers in teaching English to toddlers. The activity was conducted because the teachers did not have teaching experience or know-how in teaching English, which resulted in disorganized lesson presentation. The intervention included a two-day workshop with lessons on creating lesson plans, instructional strategies, and the use of teaching aids. The training was conducted in four stages: problem identification, program planning, implementation, and evaluation. The result provided an improvement in the understanding of lesson planning among teachers based on the higher post-test scores. Additionally, instructional aids such as flashcards, finger puppets, and picture books were introduced to enable engaging lesson presentation. The evaluation survey revealed a positive response from the participants since it mentioned the appropriateness and effectiveness of the program. Overall, this project was able to improve the ability of teachers to plan and conduct English classes effectively, ultimately leading to better English early childhood education in Aisyiyah Al Amna Playgroup.